Experimental and Simulative Investigations on a Water Immersion Cooling System for Cylindrical Battery Cells - Luo, Mingyun; Cao, Jiahao; Liu, Ninghui; Zhang, Zhengguo; Fang, Xiaoming (Frontiers in Energy Research, 2022)
High charge/discharge rates and high energy density require a greater cooling power and a more compact structure for battery thermal management systems. The Immersion cooling (direct liquid cooling) system reduces the thermal resistance between the cooling medium and the battery and greatly enhances the cooling effect of the system. However, the high viscosity and low specific heat capacity of dielectric fluid limit the cooling effect of immersion cooling. This study presents an immersion cooling system that uses water as the cooling medium. In this system, a special seal structure was designed to prevent contact between water and the battery’s electrodes. The cooling effect of the system on the battery pack was numerically studied. Even if the battery pack is discharged at 3 C rate, a small water flow rate (200 mL/min) can ensure that the maximum temperature of the battery pack falls below 50 ℃. However, a good cooling capacity will increase the temperature difference of the battery pack. The temperature difference of the battery pack is difficult to reduce to 5 ℃ until the water flow rate exceeds 1000 mL/min. Adding a buffer structure at the inlet/outlet can be reduced the negative effects of the turbulent flow and then improve the temperature uniformity of the battery pack. These findings provide a better understanding of the influencing factors of the water immersion cooling system and can help to design a better immersion cooling system.